Capture of CO2 in activated carbon synthesized from municipal solid waste compost - Karimi, Mohsen (2020)
In this study, municipal solid waste composts obtained from mechanical biological treat-ment has been considered as a source of adsorbents for CO2 capture. Three samples de-rived from the maturated compost in the municipal solid wastes were modified to produce activated carbon. The first sample was treated with sulfuric acid, the second one was thermally treated at 800 0C and the last one was modified chemically and thermally with sulfuric acid and at 800 0C. Then, the CO2 uptake capacity of prepared samples was measured through breakthrough adsorption experiments at the post combustion operation-al conditions to collect isotherm data. Also a fixed bed adsorption mathematical model was developed by applying mass and energy balances. Results showed the municipal solid wastes have an excellent capacity to be considered as source of adsorbent for CO2 capture also the mathematical model is able to predict breakthrough data.